GM-002 The patient medicines pathway: a new collaborative approach to the safe use of medicines process. (24th February 2014) - Barbier, E; Deck, L; Haddad, R; Fior, R; Lambotte, O; Noah, A; Rieutord, A
Abstract : Background: Hospitals are increasingly challenged to use medicines better, more safely and efficiently for the patient. To do so, there is a growing pressure from public authorities to harmonise practices particularly with the certification procedure. However quality management and continuous improvement have, in general, been misunderstood so far. Process-oriented management has been proved to be an interesting approach in our pharmacy department since 2010 and a decree, released in April 2011, promoting it for the medicines use process. Purpose: To define strategic objectives for quality and risk management, linked to the patient medicines pathway (PMP), in order to disseminate those concepts to the entire staff of the hospital group (HG). Materials and methods: Three hospitals form the HG with a total of about 2100 beds. The steering committee (SC) was composed of trans-HG and multidisciplinary healthcare professionals, quality and risk managers. They designed the PMP process map and a risk map using a simplified FMECA (Failure Mode Effects and Criticality Analysis) model. Another project group matched serious adverse events (SAE) analysis and PMP cartography. After that, a comparison was made of a priori and a posteriori results of risk analysis of the medicines use processes. Results: The process map and the FMECA were achieved after 8 meetings of the SC by running practical and interactive workshops. Thanks to this method, members gained an insight into the concepts of process and the a priori risk management. Finally, an electronic documentary system was designed using the institutional tool 'Blue Médi' according to the PMP cartography. We officially chose a risk manager/pharmacist duo and the ALARM (Association of Litigation And Risk Management) method to manage medicines SAE. The key step of the PMP cartography most cited in the SAE was administration. Comparison of FMECA and SAE results demonstrated some similarities about critical key steps but also differences, revealing the necessity to conduct both a priori and a posteriori analyses. From this cross analysis, we were able to identify the top 6 priorities. The SC has written a common method to disseminate the concept of process management and risk management to operators. It relies on simple, well-structured project management: i.e. define a clear target, SMART objectives, simple Gantt chart, relevant metrics chosen by operators/practitioners and respect of the time frame (3 to 6 months max). Conclusions: We designed and validated in practice a methodology aimed at educating about, and gradually implementing, a new managerial process-oriented approach, for both managers and operators. We definitely consider that it is very important for all HG healthcare workers to gain an insight into Quality and Risk Management. Our initiative will reinforce the collaborative work between healthcare professionals and facilitate the coming HG certification (2014) at a quiet, steady pace. No conflict of interest.